EFEKTIFITAS MEDIA POSTER DALAM MENINGKATKAN PENGETAHUAN SANITASI DASAR DI SDN 01 WONOSOCO UNDAAN KUDUS - David Laksamana Caesar; Bagas Aji Prasetya (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
Basic sanitation is the minimum facility needed to provide a healthy residential environment with health requirements which include the provision of clean water, toilet facilities, waste disposal, and wastewater disposal. Sanitary conditions that do not health requirements, provide opportunities for the development of diseases such as skin diseases, helminthiasis, and even diseases that can become epidemics and cause death such as diarrhea, dysentery, and so forth. To achieve optimal health status, it is necessary to have a comprehensive health program by implementing health promotion strategies. Poster media is one of the most effective media used in health promotion. This research aims to see the effectiveness of poster media in improving basic sanitation knowledge in SDN 01 Wonosoco. This type of research is an experimental study with a One Group Pretest Posttest research design. The number of samples in this study was 35 respondents. The instruments in this study used questionnaires and posters. Bivariate analysis using Paired Sample T-Test. The average pretest score on Basic Sanitation knowledge was 55.46, while the post-test average score of knowledge was 88.71. The results of the bivariate analysis revealed that there were significant differences between the pretest and posttest scores on the Basic Sanitation knowledge of SDN 01 Wonosoco students with a p-value of knowledge 0,0001 and a percentage value of 59.95. The poster media is effective in increasing students' knowledge about Basic Sanitation at SDN 01 Wonosoco